Evolution of Peak Shear Strength of Rock Fractures Under Conditions of Repetitive Dry and Wet Cycling - Guo, Baohua; Cheng, Tan; Sun, Jiehao; Tian, Shixuan; Chen, Yan; Niu, Yongbin (Frontiers in Earth Science, 2022)
The degradation of shear mechanical properties of rock fracture surfaces was determined after applying multiple dry-wet cycles. Artificially fractured feldspathic sandstone specimens were soaked in chemical solutions with pH values of 2, 7, and 12 for 3, 6, 9, 12, and 15 dry-wet cycles, followed by direct shear tests under normal stresses of 3, 6, 9, 12, and 15 MPa. The results showed that the pre-peak shear stiffness and peak shear strength of the fracture surfaces decreased, and the peak shear displacement increased progressively after cumulative dry-wet cycling treatments compared to the behavior of oven-dry rock fractures. Additionally, the pre-peak shear stiffness, peak shear strength, peak shear displacement, and residual shear strength decreased cumulatively as the number of dry-wet cycles increased. However, the chemistry of the wetting solution had little effect on mechanical behavior. Based on the Barton formula for describing the peak shear strength for rock fractures, an empirical formula for peak shear strength for irregular rock fractures under dry-wet cycling conditions is proposed by introducing a proportionality factor to describe the degree of deterioration of the rock fracture surface shear strength. The modified formula has a good fitting accuracy for the test shear strength data of sandstone fractures under dry-wet cycling conditions, which may assist in the practical estimation of the peak shear strength of rock fractures under dry-wet cycling conditions in engineering practice.